2014
DOI: 10.1128/ec.00158-13
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Cytosolic Iron-Sulfur Cluster Assembly Machinery in Blastocystis Species and Other Microbial Eukaryotes

Abstract: bThe cytosolic iron/sulfur cluster assembly (CIA) machinery is responsible for the assembly of cytosolic and nuclear iron/sulfur clusters, cofactors that are vital for all living cells. This machinery is uniquely found in eukaryotes and consists of at least eight proteins in opisthokont lineages, such as animals and fungi. We sought to identify and characterize homologues of the CIA system proteins in the anaerobic stramenopile parasite Blastocystis sp. strain NandII. We identified transcripts encoding six of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 50 publications
9
69
0
Order By: Relevance
“…1i). Recent analyses of Dre2 from other eukaryotes suggested that it was present in the LECA54, but did not resolve its specific prokaryotic origin. Taken together, these data suggest that the CIA pathway is of mainly bacterial heritage and was already in place in the LECA.…”
Section: Resultsmentioning
confidence: 99%
“…1i). Recent analyses of Dre2 from other eukaryotes suggested that it was present in the LECA54, but did not resolve its specific prokaryotic origin. Taken together, these data suggest that the CIA pathway is of mainly bacterial heritage and was already in place in the LECA.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these components are essential for viability of yeast cells, and they are conserved in virtually all eukaryotes including human cells (Seki et al, 2013;Song and Lee, 2008;Stehling et al, 2008;Stehling et al, 2012;Tsaousis et al, 2014).…”
Section: How the Cia Machinery Uses The Exported Atm1 Substrate For Fmentioning
confidence: 99%
“…As a eukaryote, Blastocystis already contains the Cia1, Cia2, MMS19, Nbp35, Nar1, and Tah18 components of the cytoplasmic iron-sulfur cluster assembly (CIA) machinery, which is distinct from Suf. (Tsaousis et al , 2014) It also is puzzling that even though Bh -SufCB can enhance E. coli SufS and SufE activity, there are no homologues of SufS and SufE in Blastocystis . Therefore it is not clear how Bh -SufCB would obtain an Fe-S cluster in the cytosol unless it interacts with the CIA machinery.…”
Section: A Role For the Suf System In The Cytosol Of Some Eukaryotesmentioning
confidence: 99%
“…(Wang et al , 2004) The sufT gene encodes a protein of unknown function although it is homologous to eukaryotic cytosolic and plastid Fe-S cluster biogenesis components (Cia2 and HCF101, respectively). (Schwenkert et al , 2010, Tsaousis et al , 2014) Attempts to delete the suf genes from M. smegmatis were unsuccessful, suggesting that the operon is essential in Mycobacteria . (Huet et al , 2005) Yeast two-hybrid assays using the M. tuberculosis genes revealed that SufB interacts with SufC and SufD in vivo.…”
Section: The Importance Of Suf In Human Pathogens: Tuberculosis Anmentioning
confidence: 99%